Hamsun og Tsjekhov—stilistisk gjenklang: Erfaringer fra mitt virke som oversetter - Pankratova, Eleonora (Nordlit, 2016)
The Norwegian term å gjendikte, meaning “to recreate”, is always my guiding principle while translating Norwegian literature into Russian. Intonation is a very important factor. For example in the earliest Hamsun novel, Bjørger (1878), it was very important for me to present a rural Norwegian atmosphere while avoiding incorrect associations and allusions and also bearing in mind strong cultural differences. While working with Hamsun’s Sværmere (1904), it was essential that I pay careful attention in conveying the right intonation and word choice, so that the reader could properly perceive the irony and humor of the novel. In many cases, the language of Chekhov, whose characters sometimes have typological resemblance to Hamsun’s, was a stylistic pattern for me. This article will use quotations from both authors to illustrate this stylistic resonance.